Update on polymer based nanomedicine - Nyström, Andreas M. (Smithers Rapra, 2012)
Polymers are one of the most applicable and clinically relevant materials for constructing nanomedical systems. These systems are expected to have a future in the clinic; nanomedical constructs will have wide implications for how we treat and diagnose society's most complex diseases, such as cancer, inflammation and genetic disorders. This update focuses on describing the fundamentals of controlled polymerisation techniques and methods for constructing advanced polymer architectures to be used in polymer based nanomedicine. This growing field is reviewed, which uses recent advances in polymer.